2018
DOI: 10.1016/j.jagp.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hippocampal Substructure Resting-State Functional Connectivity with Memory Performance in Older Adults

Abstract: Objectives Hippocampal hyperactivation marks pre-clinical dementia pathophysiology, potentially due to differences in the connectivity of specific medial temporal lobe structures. Our aims were to characterize the resting-state functional connectivity of medial temporal lobe sub-structures in older adults, and evaluate whether specific sub-structural (rather than global) functional connectivity relates to memory function. Methods In 15 adults (mean age=69 years), we evaluated the resting-state functional con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, recent studies have shown that RAR characteristics are associated with the neurobiological biological hallmarks of dementia early in the disease process (i.e., in community and pre-clinical samples) including amyloid deposition (22), medial temporal lobe atrophy (21), and cerebrovascular disease (although associations may be region specific) (19, 20). In addition, the study by Sherman et al showed that RAR disruption related to hippocampal hyperactivation (23), which is considered a component of pre-clinical dementia pathophysiology related to early memory decline (e.g., see the study by Smagula et al (38). In this context, findings from longitudinal epidemiological studies (showing RAR disruption predicts future cognitive decline) might be due to RARs already reflecting early-stage neuropathology (which was not controlled for in existing longitudinal studies).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have shown that RAR characteristics are associated with the neurobiological biological hallmarks of dementia early in the disease process (i.e., in community and pre-clinical samples) including amyloid deposition (22), medial temporal lobe atrophy (21), and cerebrovascular disease (although associations may be region specific) (19, 20). In addition, the study by Sherman et al showed that RAR disruption related to hippocampal hyperactivation (23), which is considered a component of pre-clinical dementia pathophysiology related to early memory decline (e.g., see the study by Smagula et al (38). In this context, findings from longitudinal epidemiological studies (showing RAR disruption predicts future cognitive decline) might be due to RARs already reflecting early-stage neuropathology (which was not controlled for in existing longitudinal studies).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, correction of small motions and then correction of bias field (ie, standardization of gray level values) have been performed in the preprocessing stage to increase the performance of the proposed technique. Motion correction has been provided by the open source and freely available FreeSurfer tool, which is widely used in medical practice . The technical details of the motion correction function were described in several publications .…”
Section: Proposed Methodsmentioning
confidence: 99%
“…Motion correction has been provided by the open source and freely available FreeSurfer tool, 38 which is widely used in medical practice. [39][40][41] The technical details of the motion correction function were described in several publications. [42][43][44] Briefly, when multiple source volumes are available, the function corrects small motions and then average them together.…”
Section: Preprocessing Stagementioning
confidence: 99%
“…The B 1 + homogeneous RF shim case (Fig. 5b) is currently being heavily used with the sTx mode on more than 20 NIH patient/disease studies conducted in our facility 13,14 due to its high B 1…”
Section: Experimental Verificationmentioning
confidence: 99%
“…This RF coil system is currently being used in more than 20 patient/diseasebased studies funded by NIH (National Institutes of Health). To date, the current fully implemented version of the RF coil system has helped acquire more than 1300 neuro in-vivo scans in ongoing 7T human MRI studies 13,14 .…”
mentioning
confidence: 99%